Identitas Lokal pada Penamaan “Jembatan Merah” dalam Karya Musik Keroncong - Muhammad Kusuma Wardhana (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This paper seeks to explain the term “Jembatan Merah” in Indonesia from a humanities perspective. Researchers see that the term which has become one of Indonesia's local identities contains many implied meanings rather than simply being understood as a form of denotation of a red bridge. Even the interpretation of this term in keroncong music works has contributed a lot in popularizing this term. Starting from the popularity of the Gesang keroncong music which uses the name "Jembatan Merah" in one of his works, to the emergence of various forms of musical genres adapted from the popularity of the keroncong song "Jembatan Merah" indirectly gives the stigma of labeling the term which leads to a historical tourist location. which is in Surabaya. In fact, there is no statement that can be proven by Gesang regarding the historical labeling of "Jembatan Merah". By using the meaning of identity in the concept of "cultural circuit" belonging to Stuart Hall, this research will attempt to answer the meaning of the identity of "Jembatan Merah" which is considered normal for ordinary people but very important in proving an interesting cultural phenomenon to be studied today.